Analisis Kontribusi Pendapatan Ibu Rumah Tangga Pemetik Teh Terhadap Pendapatan Keluarga di Kecamatan Bermani Ulu Kabupaten Rejang Lebong: (Studi Kasus PT. Agrotea Bukit Daun) - Della Sapira; Febri Nur Pramudya; Dodi Aprianto; Mira Yanuarti (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This research was carried out from December 2024 to January 2025. This research aims to: 1). To determine the contribution of tea picking housewives' income to family income in Bermani Ulu District 2). Calculating how much tea picking housewives contribute to family income in Bermani Ulu District 3). To determine the influence of tea picking housewives' income on family income. The methods used in this research are descriptive analysis, income analysis, contribution analysis and simple linear regression analysis. The method for determining respondents in this research uses the sample census method used, namely 15 people. Where samples were taken from all housewives who worked as tea pickers at PT. Agrotea Bukit Daun. The results of the study concluded that there was an influence between the income of tea picking housewives on family income. The income contribution of tea picking housewives at PT Agrotea Bukit Daun is 66%. The life activities of housewives who work as tea pickers at PT Agrotea Bukit Daun show that the average time spent working as a tea picker is 7 hours a day.